THE CULTURE OF SECURITY AND DEFENCE: A PROPOSAL FOR CONCEPTUAL ANALYSIS FROM A POLITICAL SCIENCE PERSPECTIVE (Journal of the Spanish Institute for Strategic Studies, 2018)
Th is paper analyses the concept of the culture of security and defencefrom the perspective of political science, studying the important implicationsand consequences of its defi nition based on the idea of politicalculture. on the other hand, also from this disciplinary viewpoint, itdiscusses the meanings of the terms culture of defence, culture of securityand defence, and culture of security. in conclusion, it suggestsa series of theoretical and conceptual proposals in order to achieve abetter and more eff ective development of this public policy.